Editorial: New Approaches to Political Leadership - Bennister, Mark (2016)
This editorial introduces the special issue and considers what the articles tell us about new approaches to political leadership. The editorial explains how each article engages with the core puzzles of political leadership and brings together many diverse theoretical and methodological approaches to the study of political leadership, a vibrant area of study currently in the midst of an academic renaissance.